Aristotle and the Hermeneutic Ontology Nowadays. Metaphysics Ix 6-10 and the Sentence of the Becoming of Being - Oñate, Teresa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
We propose to show how for the Modal Ontology of the Greek Aristotle, and according to the central logos of his First Philosophy (IX, 6-10), ontological truth has a practical and a poetic status of community historical transmission, which founds the universal and isonomic assembly of the political legislation. We will show as well how contemporary hermeneutic ontology and the French thinking of difference drink abundantly from this understanding of truth, that fully belongs to the modal-temporal ontology, which thinks of the modes of being-time of action (energeia) and power (dúnamis) in Aristotle.